R graphics cookbook - Chang, Winston (O'Reilly Media, 2012)
This practical guide provides more than 150 recipes to help you generate high-quality graphs quickly, without having to comb through all the details of R's graphing systems. Each recipe tackles a specific problem with a solution you can apply to your own project, and includes a discussion of how and why the recipe works. Most of the recipes use the ggplot2 package, a powerful and flexible way to make graphs in R. If you have a basic understanding of the R language, you're ready to get started. Use R's default graphics for quick exploration of data Create a variety of bar graphs, line graphs, and scatter plots Summarize data distributions with histograms, density curves, box plots, and other examples Provide annotations to help viewers interpret data Control the overall appearance of graphics Render data groups alongside each other for easy comparison Use colors in plots Create network graphs, heat maps, and 3D scatter plots Structure data for graphing.
Online resource; title from PDF title page (Safari, viewed Jan. 22, 2013). - Print version record
Keywords: R (Computer program language); Information visualization; R (Langage de programmation); Visualisation de l'information; COMPUTERS; Programming; Object Oriented